Analysis of the Effectiveness and Efficiency of the Sales Budget as a Revenue Control Tool at the Rose Collection Palu Boutique - Rio Bagas Maulana; Sugianto; Nurhayati Haris; Rahmi Syafitri (Universitas Muhammadiyah Palu, 2026)
This study aims to analyze the effectiveness of the sales budget and the efficiency of operational costs as an instrument of revenue control at the Rose Collection Palu Boutique. The main problem studied is focused on the variance between the budget target and financial realization that risks the stability of cash flow. The variables studied include revenue effectiveness and operational cost efficiency. The research methodology used is quantitative descriptive with variance analysis techniques to dissect financial performance systematically. Financial statement data is collected, tabulated into comparative tables, and calculated using management accounting ratios to provide accurate interpretation of financial conditions. The results of the study show that Rose Collection Palu Boutique has applied the principles of sound management accounting with a revenue effectiveness ratio of 96% (effective category) and a cost efficiency ratio of 80.4% (efficient category). This finding confirms that even though the revenue target is not fully achieved, the surplus from cost savings is able to cover the shortfall so that financial performance in the net bottom line is maintained. The managerial implications show that the budget has functioned optimally as a performance driver as well as a cost control tool. This research contributes to boutique owners in preparing more precise financial planning and becomes a scientific reference for the development of management accounting studies in the MSME sector in Central Sulawesi.